2019
DOI: 10.3389/fnagi.2019.00098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Exercise on Inflammatory Markers in Healthy Middle-Aged and Older Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Chronic inflammation plays a significant role in accelerating the aging process and is closely associated with the initiation and progression of a broad range of age-related diseases. Physical exercise is considered beneficial in alleviating these conditions, but the effects of aerobic exercise on inflammatory markers in a healthy population should be furtherly clarified. Objective: The purpose of this systematic review and meta-analysis was to evaluate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 46 publications
8
114
0
2
Order By: Relevance
“…Although acute exercise was found to trigger a transient increase in oxidative stress and proinflammatory cytokines, chronic exercise was shown to induce a systemic anti-inflammatory response not only in the recovery period but also in the long term, an effect hypothesized to partially mediate its health benefits [ 9 , 238 ]. In healthy individuals subjected to aerobic exercise interventions, systematic reviews and meta-analyses have found decreased circulating levels of TNF-α, IL-6, and CRP [ 249 ], as well as increased levels of the anti-inflammatory cytokine IL-10 [ 250 ]. A meta-analysis focusing specifically on individuals with T2DM has also described decreased levels of IL-6 and CRP with aerobic exercise interventions [ 227 ], which emphasizes that the anti-inflammatory properties of exercise are strong regardless of preexisting metabolic status.…”
Section: An Integrative Overview Of Exercise-induced Factors Influmentioning
confidence: 99%
“…Although acute exercise was found to trigger a transient increase in oxidative stress and proinflammatory cytokines, chronic exercise was shown to induce a systemic anti-inflammatory response not only in the recovery period but also in the long term, an effect hypothesized to partially mediate its health benefits [ 9 , 238 ]. In healthy individuals subjected to aerobic exercise interventions, systematic reviews and meta-analyses have found decreased circulating levels of TNF-α, IL-6, and CRP [ 249 ], as well as increased levels of the anti-inflammatory cytokine IL-10 [ 250 ]. A meta-analysis focusing specifically on individuals with T2DM has also described decreased levels of IL-6 and CRP with aerobic exercise interventions [ 227 ], which emphasizes that the anti-inflammatory properties of exercise are strong regardless of preexisting metabolic status.…”
Section: An Integrative Overview Of Exercise-induced Factors Influmentioning
confidence: 99%
“…Secondly, it can increase the level of immunoglobulins (IgA, IgM, IgG), particularly IgA because of its vital role against lung infections [12e15]. Lastly, it can regulate the level of C-reactive proteins (CRP), through inducing a short-term small increase [16e18] to fight lung infections and a longeterm decrease to inhibit any decrease in lung functions [19,20], and lowering anxiety and depression to improve the immunity by re-balancing T-helper-1/T-helper-2 21À27 .…”
Section: And 2)mentioning
confidence: 99%
“…Patients with COVID-19 have very high levels of CRP [1,74]. Increasing the aerobic capacity plays an interesting role in regulating the CRP levels by producing a short-term small increase in CRP levels [16e18] to fight lung infections and a long-term decrease in CRP levels [19,20] to prevent the decrease in lung functions.…”
mentioning
confidence: 99%
“…Exercise interventions have been shown as potential mediators of improved inflammatory profiles. A recent meta-analysis of randomized controlled trials, evaluating 1,138 healthy middle-aged and older patients, showed improvements in tumoral necrosis factor α, IL-6, and CRP levels in individuals exposed to aerobic exercise training, when compared with those in non-exercising controls ( Zheng et al, 2019 ). These results are following a previous meta-analysis evaluating the effects of exercise on CRP levels that, in sensitivity analyses, also showed reduced concentrations of this inflammatory marker in patients with established CVD and type 2 diabetes ( Fedewa et al, 2017 ).…”
Section: Blood Rheology Inflammation and The Role Of Exercisementioning
confidence: 99%